IMAGE OF MARY OF BETHANY AN INSPIRATION FOR MYSTICISM - Aleksandra Nalewaj (Forum Teologiczne)
The purpose of this article is to attempt to interpret Mary's gesture at the feast in Bethany, that is, anointing Jesus' feet with precious nard and rubbing them with her hair (Jn 12:3). The act of Martha's sister and Lazarus is logically incomprehensible; moreover, it breaks the conventions of the time. In the following steps, we will discuss the closer and further context of the pericope Jn 12:1-11, followed by the ritual of anointing in the ancient world. Analysing the Johannine text from an exegetical and theological angle will allow us to reveal Mary's role in the narrative as servant and disciple. Recognising the bridal metaphor in Jn 12:1-11 brings out the meaningful depth of the text. The image of the contemplative and generous Mary, symbolising the Church as the bride of Christ, is an inspiration for mysticism.